Facilitating pathways to care: A qualitative study of the self‐reported needs and coping skills of caregivers of young adults diagnosed with early psychosis. Issue 4 (11th February 2020) - Cheng, Sunny Chieh; Backonja, Uba; Buck, Benjamin; Monroe‐DeVita, Maria; Walsh, Elaine
Accessible summary: What is known on the subject?: In clinical psychiatry and mental health nursing practice, family caregivers are known to provide the bulk of care and play an important role in facilitating recovery outcomes for their loved ones diagnosed with psychosis. Providing services and interventions to family caregivers is as important as to patients in the early stage of psychotic experience for having a beneficial impact on the patients' clinical and social outcomes. Limited qualitative research has focused on family caregivers' subjective views of what they need during the critical period to identify early warning signs and connect their loved ones to professional help as they have no prior experience in caring for persons with psychosis. What this paper adds to existing knowledge?: Using qualitative analysis of family caregiver focus groups, this manuscript provides readers in clinical nursing practice with an understanding of family caregivers' lived experiences of supporting their loved one diagnosed with early psychosis. Understanding family caregivers' caregiving unmet needs in supporting their loved one diagnosed with early psychosis could inform both the technology‐assisted intervention development and nursing practice in improving family‐centred care and facilitate self‐management practice. Implications for mental health nursing: Psychiatry and mental health nursing has long been engaged with the health and well‐being of individuals with psychosis and supporting their families in the development, evaluation and implementation of innovative approaches to patient and family education. Digital technologies designed to deliver tailored intervention for family caregivers are underdeveloped, and the present study identifies a number of potential features that could comprise technology to meet the needs of this population. Abstract: Introduction: Caregivers play a critical role in detecting and managing psychotic symptoms before young people diagnosed with early psychosis present to care. Little is known about the specific needs of caregivers in navigating pathways to care for their loved one. Aim: The purpose of this study was to understand the needs of family caregivers and their ways of coping on the pathway to care for early psychosis. Method: Twenty family caregivers of individuals diagnosed with early psychosis participated in three focus groups that explored caregiving needs provision for early psychosis. Thematic analysis was conducted. Results: We identified four major themes: education and skill training; raising wider awareness, such as police offers and teachers; adopting technologies for coping; and effective coping strategies. Implications for practice: These findings provide important insights into caregiving needs and the ways for nurses to address those needs and better equip carers to recognize early symptoms, monitor behaviour changes and navigate care to support people with first‐episode psychosis. Nursing researchers can use the information to develop on‐demand and tailored family‐centred intervention in addressing caregivers' needs in education, increasing awareness of early psychosis and fostering effective coping strategies.